2018
DOI: 10.21833/ijaas.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal effects of six herbal extracts against Aspergillus sp. and compared to amphotericin B and nystatin

Abstract: Aspergillus is a filamentous fungus of wide distribution having widespread species diversity. Among pathogenic species of Aspergillus, Aspergillus fumigatus, Aspergillus niger, and Aspergillus flavus are regarded as the most important pathogenic agents. The aim of this research is to study the antifungal effects of Artemisia dracunculus L, Achillea wilhelmsii C. Koch, Bunium persicum, Cuminum cyminum L, Zataria multiflora Boiss, and Satureja hortensis extracts against Aspergillus Sp. The herbal extracts were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…Previously, Amjad et al [49] reported that the methanolic extract of Achillea wilhelmsii C. Koch flowers has excellent antifungal activity against 20 Candida albicans strains. In contrast to the current work, Tajehmiri et al [50] found that three fungal species Aspergillus fumigatus, Aspergillus niger, and Aspergillus flavus were susceptible to A. wilhelmsii extract. Antimicrobial activity of Achillea wilhelmsii extract was also investigated by Bashi et al [28], and their findings showed no obvious inhibitory effect on Aspergillus niger.…”
Section: Discussioncontrasting
confidence: 99%
“…Previously, Amjad et al [49] reported that the methanolic extract of Achillea wilhelmsii C. Koch flowers has excellent antifungal activity against 20 Candida albicans strains. In contrast to the current work, Tajehmiri et al [50] found that three fungal species Aspergillus fumigatus, Aspergillus niger, and Aspergillus flavus were susceptible to A. wilhelmsii extract. Antimicrobial activity of Achillea wilhelmsii extract was also investigated by Bashi et al [28], and their findings showed no obvious inhibitory effect on Aspergillus niger.…”
Section: Discussioncontrasting
confidence: 99%
“…The commercial antifungal drug amphotericin B has been selected for the comparative study of molecular docking results. MIC of amphotericin B (1.8 µl/ml) 39 was comparatively higher than the ZOEO (0.6 µl/ml) (Fig. 2 a) A comparative study of binding energy, inhibition constant and ligand efficiency has been shown in Table 3 .…”
Section: Resultsmentioning
confidence: 96%
“…[ 49 ] showed that Spinacia oleracea extracts were effective antifungals by diminishing the conidia of toxigenic A. flavus . The extracts had 19.6% saponins, flavonoids, terpenoids, tannins, alkaloids, and glycosides and the antifungal properties of the extracts of Artemisia dracunculus , Achillea wilhelmsii , Bunium persicum , C. cyminum , Zataria multiflora Boiss, and Satureja hortensis were studied against A. niger , A. fumigatus , A. flavus [ 50 ], and Candida albicans [ 51 ]. Among the extracts tested, A. wilhelmsii and Z. multiflora Boiss were the most effective antifungals.…”
Section: Antifungalmentioning
confidence: 99%